Nursing and Social Change. - Baly, Monica E. (Monica Eileen) (Routledge, 1994)
Third edition of an invaluable text examining how nursing has developed from its beginnings to the present day. Fully updated with ten new chapters, contributions take into account the challenges facing nurses today.